1999
DOI: 10.1046/j.1365-2826.1999.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in NADPH‐d Staining in the Paraventricular and Supraoptic Nuclei During Pregnancy and Lactation in Rats: Role of Ovarian Steroids and Oxytocin

Abstract: Staining for nicotinamide adenine dinucleotide phosphate diaphorase (NADPH-d), a histochemical marker for nitric oxide synthase (NOS), is increased in the supraoptic (SON) and paraventricular (PVN) nuclei in late pregnant rats. To determine whether increases in staining were evident at other times during pregnancy and lactation the number of cells that stained for NADPH-d in the SON and PVN in rats on days 4, 12, 16, and 22 of pregnancy and on days 4, 12, and 20 of lactation was compared to that in virgin fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
37
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 63 publications
5
37
0
Order By: Relevance
“…This is the first study to show that this febrile response can be restored and that brain NO plays a determining role in the mechanism of fever suppression. This NO-mediated mechanism is consistent with previous reports that the expression of NOS within the brain is increased during late pregnancy (38,47,48) and that central NO donors can inhibit LPS-induced fever (21). The dose of L-NMMA that we used did not cause significant hyperthermia by itself in either day 19 and 20 pregnant, day 15 pregnant, or virgin female rats, demonstrating that the febrile response in near-term dams was due to a restoration of the neuroimmune response to LPS and not a nonspecific response to L-NMMA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is the first study to show that this febrile response can be restored and that brain NO plays a determining role in the mechanism of fever suppression. This NO-mediated mechanism is consistent with previous reports that the expression of NOS within the brain is increased during late pregnancy (38,47,48) and that central NO donors can inhibit LPS-induced fever (21). The dose of L-NMMA that we used did not cause significant hyperthermia by itself in either day 19 and 20 pregnant, day 15 pregnant, or virgin female rats, demonstrating that the febrile response in near-term dams was due to a restoration of the neuroimmune response to LPS and not a nonspecific response to L-NMMA.…”
Section: Discussionsupporting
confidence: 93%
“…However, these increases can be blocked by the nonspecific COX inhibitor indomethacin (31, 44), indicating interactions between COX and NO activity. Oestrogen and progesterone, secreted during pregnancy, increase expression of endothelial NOS within cerebral blood vessels (33), and the neuronal NOS isoform is also increased in the hypothalamus during the late stages of pregnancy (38,47,48).There is growing evidence that NO is involved in thermoregulation through neural signaling (31,42). Neurons containing NOS have been identified in the medial preoptic area (3), a key integrative site for thermoregulatory signals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At this time, plasma progesterone levels would likely be elevated above that of nonpregnant rats. In contrast, in pregnant rats on the day of parturition after progesterone falls and is low or in rats where progesterone is withdrawn after hormone treatment to mimic the time of parturition, nNOS activity in both the SON and PVN is increased (38,53). Together, these data suggest that decreased nNOS expression in the PVN during pregnancy may be attributed to high progesterone levels rather than high estrogen levels.…”
Section: Discussionmentioning
confidence: 86%
“…It has been reported that physiological stimuli, such as pregnancy and lactation, could increase NOS expression in HNS. These activity-dependent enhancements never lead to neuronal death in HNS [36,37]. Taken together, it seems that enhanced NOS/NO induced by physiological stimuli or pathological stimulation of axonal injury may not cause neuronal death.…”
Section: Discussionmentioning
confidence: 90%